2014
DOI: 10.1038/nature13572
|View full text |Cite
|
Sign up to set email alerts
|

eIF4F is a nexus of resistance to anti-BRAF and anti-MEK cancer therapies

Abstract: In BRAF(V600)-mutant tumours, most mechanisms of resistance to drugs that target the BRAF and/or MEK kinases rely on reactivation of the RAS-RAF-MEK-ERK mitogen-activated protein kinase (MAPK) signal transduction pathway, on activation of the alternative, PI(3)K-AKT-mTOR, pathway (which is ERK independent) or on modulation of the caspase-dependent apoptotic cascade. All three pathways converge to regulate the formation of the eIF4F eukaryotic translation initiation complex, which binds to the 7-methylguanylate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
273
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 307 publications
(313 citation statements)
references
References 20 publications
19
273
1
Order By: Relevance
“…Consistent with this hypothesis, we observed that PDCD4-deficient HCT116 cells by shRNA expression were more susceptible than PDCD4-proficient cells to death after treatment with the flavagline FL3 (Fig. 3), which is a specific and potent eIF4A inhibitor (19,28). We also found that treatment with FL3 substantially increased the susceptibility of STAT1-proficient HCT116 cells to death compared with STAT1-deficient HCT116 cells (Fig.…”
Section: Stat1 Sensitizes Hct116 Cells To Death By Eif4a Inhibitionsupporting
confidence: 75%
See 2 more Smart Citations
“…Consistent with this hypothesis, we observed that PDCD4-deficient HCT116 cells by shRNA expression were more susceptible than PDCD4-proficient cells to death after treatment with the flavagline FL3 (Fig. 3), which is a specific and potent eIF4A inhibitor (19,28). We also found that treatment with FL3 substantially increased the susceptibility of STAT1-proficient HCT116 cells to death compared with STAT1-deficient HCT116 cells (Fig.…”
Section: Stat1 Sensitizes Hct116 Cells To Death By Eif4a Inhibitionsupporting
confidence: 75%
“…The PDCD4 shRNA was expressed from psiRNA-hH1hygro G2 vector (18). Human IFNa and IFNg was obtained from Biosource (Invitrogen), whereas treatment with FL3 was performed as described previously (19).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…S7A), and confirmed by a proximity ligation assay (PLA) (37), which allows direct visualization of in vivo protein-protein interactions (Fig. 6L).…”
Section: Ctcf Interacts With Rad51 and Is Necessary For Formation Of mentioning
confidence: 99%
“…Inhibition of eIF4A function with hippuristanol synergized with anti-BRAF or anti-MEK inhibitors and the data suggested that combinations of drugs targeting BRAF and eIF4A (as part of eIF4F) would be sufficient to overcome most resistance mechanisms in BRAF (V600)-mutant cancers and provide new treatment options for patients with this aggressive cancer. 12 However, despite these studies, the frequency and role of increased eIF4A1 activity in tumorigenesis has not been extensively investigated. Modelska et al carried out an important large-scale study to determine the clinical significance of expression of eIF4A1 and its modulators in breast cancer by scoring tissue microarrays derived from~4000 patients.…”
mentioning
confidence: 99%